Assessment System of Halal Product Assurance Implementation in Indonesian Companies Using ID3 and Forward Chaining Algorithm - Adline Twice Tobing, Fenina; Kusnadi, Adhi; Harjono, Marco Keegan Shandry; Tjoang, Stephen (Publisher Cv. Inara, 2023)
The majority of the population in Indonesia practices Islam, making halal products important and necessary to meet the rights and needs of Muslim consumers in Indonesia. Therefore, a halal assurance system is required, not only for obtaining halal certification, but also for maintaining continuity in halal production. The existing halal assurance system has been manual, hence the need for an automated computer-based information system that can assess the halal assurance system implemented by companies. This can make it easier and faster for novice users to assess the implementation of halal practices in a company. The ID3 algorithm is used to create decision trees, and the forward chaining algorithm is used for comparison. The web-based system is developed using PHP language and MySQL for data storage. Testing the system by comparing the final results with the manual calculations, as well as using the ID3 and forward chaining algorithms, yields the same results, indicating the successful development of assessment system of halal product assurance. In addition, user satisfaction testing resulted in a score of 87.34%, indicating that users are highly satisfied with the JaminHalal information system.